Differential pulse voltammetric determination of nitrite with gold ultramicroelectrode - da Silva, S. M.; Mazo, L. H. (Wiley-Blackwell, 1998)
The application of disk shaped gold ultramicroelectrode for nitrite determination with and without addition of supporting electrolyte was studied using the differential pulse voltammetric method. The well-defined peak for nitrite oxidation near 0.8V (vs. Ag/AgCl reference electrode) was used to obtain analytical plots in the concentration range from 0.1 to 0.6 mmol L-1 and from 10.0 to 50.0 mu mol.L-1. The calculated detection limit was 0.65 mu mol.L-1 in purified water, in the absence of supporting electrolyte, with relative standard deviation of 1.36% (n=6) for analyzing 10.0 mu mol L-1 nitrite solutions, and accuracy of 100.9 %, based on recovery studies. The application of this analytical method to mineral and river water samples of natural pH also showed improved sensitivity when compared with the linear sweep voltammetric method previously reported.
Keywords: nitrite; ultramicroelectrodes; natural water; differential pulse voltammetry